Recruiting the Human Pathological Specimen Scientifically and Rightly for Cancer Molecular or Biological Researches (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: recruiting the human pathological specimen; cancer research; genetics; research promotion; quality control; S T R E G A